Use of Intravenous Amiodarone in the Treatment of Nifekalant-Resistant Arrhythmia: A Review of 11 Consecutive Cases with Severe Heart Failure - Tohru Ujihira; Hiroshi Ito; Hiroshi Morita; Takeshi Tada; Kunihisa Kohno; Yoshiki Hata; Kengo Fukushima Kusano; Koji Nakagawa; Kazufumi Nakamura; Satoshi Nagase; Tohru Ohe; Masato Murakami; et al. (MDPI AG, 2011)
Background: Both nifekalant hydrochloride (NIF), a selective IKr blocker, and intravenous amiodarone (AMD), a multi-channel (including IKr blocking) blocker, have been reported to be efficacious for refractory arrhythmias. However, the optimal use of those antiarrhythmic drugs for refractory arrhythmia with severe heart failure has not been established. Intravenous AMD might be effective for arrhythmias refractory to NIF in patients with severe heart failure. Here, we report that intravenous amiodarone was effective in the treatment of nifekalant-resistant in a group of arrhythmia patients with severe heart failure. Methods: Eleven severe heart failure patients who had received intravenous AMD for treatment of NIF-resistant arrhythmias were included in this study, and retrospective analysis was performed. Clinical efficacy (terminative and preventive effects on arrhythmia) of intravenous AMD was evaluated. Results: All cases were emergent cases and had depressed left ventricular ejection fraction (30 ± 13%). Clinical arrhythmias were ventricular fibrillation (VF) in four patients, ventricular tachycardia (VT) in six patients, and atrial fibrillation (AF) in one patient. NIF was administered to all patients by intravenous injection. After administration of NIF, VT/VF/AF was terminated in seven of the 10 patients, but a preventive effect was not obtained in any of the patients (NIF-resistance). Intravenous AMD (maintenance dose: 484 ± 166 mg/day) was effective both in termination (80%) and in prevention (80%) of VT/VF events in those patients. It was also effective in termination (80%) and prevention (60%) of AF events refractory to NIF. During continuous AMD administration, no significant adverse effects or proarrhythmic effects were observed in any of the patients. Five patients died within one month, but there was no arrhythmic deaths. Conclusions: Intravenous AMD was effective in NIF-resistant lethal arrhythmias and was relatively safe in emergent cases with severe heart failure.